Perfect Storm : Climate Change and Tourism - Cevik, Serhan (IMF Working Papers; Working Paper, 2020)
While the world's attention is on dealing with the COVID-19 pandemic, climate change remains a greater existential threat to vulnerable countries that are highly dependent on a weather-sensitive sector like tourism. Using a novel multidimensional index, this study investigates the long-term impact of climate change vulnerability on international tourism in a panel of 15 Caribbean countries over the period 1995-2017. Empirical results show that climate vulnerability already has a statistically and economically significant negative effect on international tourism revenues across the region. As extreme weather events are becoming more frequent and severe over time, our findings indicate that the Caribbean countries need to pursue comprehensive adaptation policies to reduce vulnerabilities to climate change.